Empathy but not musicality is at the root of musical reward: A behavioral study with adults and children. (November 2022) - Carraturo, Giulio; Ferreri, Laura; Vuust, Peter; Matera, Flavia; Brattico, Elvira
Music is one of the most pleasurable human experiences. However, the determinants of the variation in individual sensitivity to musical reward are not yet fully unraveled. Empathy has been identified as a determinant of musical affect, including consciously experiencing pleasure from listening to sad music. Additionally, higher musical expertise may enhance pleasurable responses to music, whereas aging decreases individual sensitivity to musical pleasure. We conducted a study to investigate the contribution of empathy and musical abilities on musical pleasure, measured by Interpersonal Reactivity Index, Musical Ear Test, and Barcelona Musical Reward Questionnaire, respectively. To this purpose, we performed a developmental comparison between 48 children (9–11 years old) and 42 adults (18–32 years old). Our findings suggest that individual sensitivity to musical reward is positively correlated with empathy trait in both adults and children, but not with musical abilities. However, when inserted in a regression model including empathy, musical abilities are also predictive of musical reward, but only among adults. These results show that empathy plays a crucial role in determining the individual sensitivity to music reward, whereas musical abilities are less influential. More broadly, this study contributes to shed light on the determinants of the emotional responses to music affect.